Upaya Meningkatkan Hasil Belajar Ekonomi dengan Menggunakan Model Pembelajaran CIRC (Cooperative Integrated Reading and Composition): Efforts to Improve Economic Learning Outcomes Using the CIRC Learning Model (Cooperative Integrated Reading and Composition) - Iin Nurbudiyani; Bertiana Bertiana (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This study aims to: (1) Know the activity of students during the economic learning process by using the CIRC (Cooperative Integrated Reading and Composition) learning model in the X-10 class of SMA 4 Palangka Raya, (2) Knowing the increase in economic learning outcomes using models learning CIRC (Cooperative Integrated Reading and Composition) in class X-10 students of SMA Negeri 4 Palangka Raya. The subjects in this study were all students of class X-10 of SMA 4 Palangka Raya, totaling 34 students. Where data collection uses observation and test sheets. Data analysis techniques use mastery learning individually and the percentage of mastery learning in classical. The results showed that: (1) The ongoing education of students in the X-10 class of SMA 4 Palangka Raya with an average in the first cycle of 2.86 was included in the sufficient category and in the second cycle the average value increased to 3.73 in the excellent category. (2) The learning outcomes of class X-10 students of SMA Negeri 4 Palangka Raya increased, from the results of the pre-test of the average score of 61.17 with classical completeness of 26.47%, the results of post-test I cycle average of 77.5 with integrity the conventional 52.94% and in the post-test cycle II the average value was 87.05 with classical completeness of 88.32%.